2006
DOI: 10.1159/000089701
|View full text |Cite
|
Sign up to set email alerts
|

Predation and Cathemerality

Abstract: The removal, or absence, of predatory species could be a contributing proximate factor to the rise of primate cathemerality. But predators themselves can also be cathemeral, so cathemerality could well be an evolutionary stable strategy. From a comparative perspective, it appears that the effect of predatory species cannot provide a unitary explanation for cathemerality. Varying distributions and population densities of predators, especially raptors, may be key factors in owl monkey (Aotus) cathemerality, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 131 publications
1
14
0
2
Order By: Relevance
“…Hypotheses that invoke predation risk to explain cathemerality (Colquhoun 2006) may also be applicable here. Although SCI is home to nocturnal predators, such as owls (Parga and Lessnau 2005), there are no known mammalian predators that would hunt lemurs at night, such as the fossa, wild cats, or civets that exist in Madagascar (Gould and Sauther 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypotheses that invoke predation risk to explain cathemerality (Colquhoun 2006) may also be applicable here. Although SCI is home to nocturnal predators, such as owls (Parga and Lessnau 2005), there are no known mammalian predators that would hunt lemurs at night, such as the fossa, wild cats, or civets that exist in Madagascar (Gould and Sauther 2007).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to predation risk and cathemerality (Colquhoun 2006), the likely differences in predation pressure between Madagascar and SCI (Parga and Lessnau 2005) may make L. catta on SCI more likely to show nocturnal ranging than L. catta in the wild. The transition between nocturnality and diurnality hypothesis for cathemerality (van Schaik and Kappeler 1996) is difficult to test so will not be evaluated here.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lemur catta are generally considered to be diurnal (Sauther et al, 1999) but Donati et al (2013) and Lafleur (2012) reported them to be cathemeral. Explanations range from predator presence or absence, to energy expenditure, thermoregulation, and competition (Curtis and Rasmussen, 2002;Kappeler and Erkert, 2003;Colquhoun, 2006;Donati et al, 2007Donati et al, , 2009Donati et al, , 2010. All of these findings are based on activity collected by direct observation, activity loggers, and camera traps, but light exposure patterns as they may affect their biological rhythms in the animal's natural habitat were not measured.…”
mentioning
confidence: 99%
“…Many primates employ a cryptic strategy to avoid detection by predators [Colquhoun, ; Fichtel, ; Isbell, ; Miller & Treves, ]. We suggest that group fission and low levels of social behavior observed in Kloss gibbon groups in the Peleonan is part of a cryptic behavioral strategy to avoid detection by hunters.…”
Section: Discussionmentioning
confidence: 99%